SOSIALISASI TEKNIK PENANGKARAN PENYU BERBASIS EKOWISATA DI PANTAI GUGOP KECAMATAN PULO ACEH KABUPATEN ACEH BESAR PROVINSI ACEH - Rika Astuti (Jurnal Marine Kreatif, 2018)
Turtles are marine reptiles that inhabit seagrass ecosystems and are able to migrate deeply along the Indian Ocean, Pacific Ocean to Southeast Asia. Turtles are scattered in tropical and subtropical waters mostly found in Indonesian waters, especially in Aceh waters. The west coast of Aceh Besar, especially Pulo Aceh currently has potential as a residence for several turtle populations. Some of the turtle species that often lay their eggs on this beach are turtles, leatherback turtles and green turtles. The purpose of this dedication is to provide understanding to the Pulo Aceh Ecotourism Institute (LEPA) and communities around Pulo Aceh to understand the importance of turtle conservation, and to implement turtle breeding techniques for ecotourism development in good Pulo Aceh and sustainability. This devotional activity is carried out for two days, ie from Saturday to 10 March to Sunday 11 March 2018 held at Gugop Beach, Pulo Aceh, Aceh Besar District, Aceh Province. The approach taken in this activity is the persuasive socialization and the direct practice of turtle conservation techniques and the release of sea turtles attended by tourists from various regions, government agencies, non-governmental organizations and academics in Aceh. Turtle turtles are released as much as 270 head of 480 total tail, which consists of 2 types; namely Turtle Lekang as many as 353 heads, which released 170 tails. While the green turtle of 127 tails, which is released only 100 tails. The abandoned hatchlings are in a breeding location aimed at ecotourism and research for academics to conduct research on these endangered and endangered animals.